Evaluasi Implementasi Aplikasi Primary Care (Pcare) di Klinik Laras Hati - Agung Kurniawan; Denny Adrian Mustika; Rizal Chandra Muhammad; Susanti Catur Putri (Jurnal Kesehatan Vokasional, 2019)
Background: Primary Care (Pcare) application is an information system designed and developed to serve patients using BPJS Health. This Pcare application has been used at the Laras Hati Clinic since 2014, but until now there has never been an evaluation regarding the performance, efficiency and control of the Pcare application.Objective: The purpose of this study is to evaluate the implementation of Pcare Applications at the Laras Hati Clinic.Method: This type of research is descriptive with a qualitative approach. The research design used was case study. The subjects of this study were medical record officers, midwives, and pharmacy officers. this research has been carried out since August 2018 until September 2018. The validity of the data used is using Triangulation of Resources and TechniquesResult: The Pcare application has been used in the Laras Hati clinic since 2014. However, there are still frequent errors and long loading, the control system used has used a username and password but there are still parties who do not have the authority to access and use the Pcare application, and resource use (material and human) is in accordance with needsConclusion: Pcare application has been used at the Laras Hati Clinic since 2014, but there are still some problems that cannot be resolved